Effects of Land Use Change on Banana Production: A Case Study of Imenti South Sub-County of Meru County in Kenya - Kevin A. Nyamamba; Tom O. Ouna; Hellen Kamiri; Erwin Pane (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Most high agricultural potential regions in Kenya such as Imenti South (Meru County) have exceeded their population density and have been associated with sharp decline in farm productivity. There has been a systematic transformation of land use for banana production in the area. This has led to reduction in land acreage under other crops and increase in land acreage under banana farming. This study focused on land use and banana production trends between the years 2000 to 2019 in Imenti South. To achieve the objective, the study used mixed research design that involved qualitative and quantitative approaches. A sample size of 377 respondents was identified using simple random sampling. Banana yields and land acreage data were obtained from Imenti South Agricultural office for the study period. The main research instruments were questionnaires for households and key informants. Majority of the respondents (72%) in the study region admitted to have changed the land use and type of crops they have been farming during the study period whereas 28% changed from other crops to banana farming. Land acreage and banana production have been increasing during the study period in the area. The study revealed there is positive and statistically significant relationship (r = .617; p = .004) between land under banana and production. The study recommends that stakeholders in County governments should establish departments that independently identify, analyses, monitor and educates the famers on the new technologies that improves and increases banana production